A Comparative Study of Topical Versus Peribulbar Anaesthesia in Phacoemulsification Cataract Surgery and Implantation of Intraocular Lens - Divya Vakharia; Suvarna K Gokhale (Journal of Clinical Research and Ophthalmology - Peertechz Publications, 2015)
Introduction: This study was conducted for evaluating and comparing levels of patient discomfort during phacoemulsification and intraocular lens implantation under topical and peribulbar anesthesia and comparative assessment of intra-operative complications. Methods: It is a hospital based comparative study on patients who underwent phacoemulsification from January'2015 to March'2015. Patients were randomly distributed to peribulbar or topical anesthesia. Parameters like age, surgery duration, blood pressure, oxygen saturation and intraoperative pain were compared in two groups. Results: 51 patients underwent phacoemulsification under topical anesthesia and 49 patients underwent phacoemulsification under peribulbar anesthesia. No statistical differences were found in surgery duration, intra-operative complications, pain, blood pressure or Oxygen saturation (SPO2). Topical group did not require additional subconjunctival injection. 4/49 (8.16%) in peribulbar group required additional topical anesthesia. This was statistically significant (p=0.04). Anesthesia related complications were only seen in peribulbar group. Conclusion: Surgical complications and patient comfort did not differ in two groups.There is no significant difference in topical and peribulbar anesthesia with respect to intra-operative pain level and intra-operative complications. Also topical anesthesia is minimally invasive. In view of results obtained, study suggests usefulness of topical anesthesia as compared to peribulbar anesthesia for cataract surgeries.